Role of Zakat in Economic Development | دور الزكاة في التنمية الاقتصادية - Jamaluddin Ahmad Kholiq (Al-Zahra : Journal for Islamic and Arabic Studies, 2014)
This paper concludes that the concept of zakat in Islamic economics has a significant rolein developing community which is not found in conventional economic concept. Zakat isa solution for poverty and unemployment. It prevents the use of non-productive fund,and encourage investment; as distributive justice. This paper uses both classical andmodern references, related to the theory of modern Islamic economics. The research isconducted based on comparative and critical reading on both classical and modernreferences.